Induction of Apoptosis in Glioma Cells Requires Cell-to-Cell Contact with Human Umbilical Cord Blood Stem Cells - Gondi, Christopher S. (2010)
We have previously demonstrated the multipotent nature of human umbilical cord blood stem cells (hUCB). In this study, we have attempted to show the use of hUCB in glioma therapy. We used hUCB enriched in CD44 and CD133 cells for our studies and observed that glioma cells co-cultured with hUCB undergo apoptosis. To prove the role of cell-to-cell contact in the induction of apoptotic events, we used a modified 0.22 μm Boyden’s chamber where the upper surface was used to culture glioma cells (SNB19 or U87) or xenografts (4910 or 5310) and the lower surface to culture hUCB. TUNEL assay was carried out to determine the degree of apoptotic induction and we observed that glioma or xenograft cells co-cultured with hUCB had a higher number of TUNEL-positive characteristics (63±6%) compared to the controls. Further, we co-cultured glioma cells labeled with lipophilic green fluorescent dye and hUCB labeled with lipophilic red fluorescent dye. FACS analysis of cells collected from the upper and lower surfaces revealed that glioma cells had taken up red fluorescent dye from the stem cells (70±3%) when compared to glioma cells co-cultured with fibroblast cells (15±4%). The apoptotic events in the glioma and xenograft cells co-culterd with hUCB were also confirmed by western blot analysis for the cleavage of PARP and activation of caspase-8. In addition, elevated levels of CHK-2 levels and downregulation of MAP2K1 were observed in glioma cells co-cultured with hUCB indicating the DNA damage and decrease in cell survival. Nude mice, intracranially implanted with luciferase-expressing U87 cells followed by implantation of hUCB or human fibroblast cells showed retardation of intracranial tumors in hUCB-implanted mice. Taken together, these results demonstrate that hUCB have therapeutic potential with possible clinical implications.